2020
DOI: 10.1093/conphys/coaa098
|View full text |Cite
|
Sign up to set email alerts
|

Inter-population differences in salinity tolerance of adult wild Sacramento splittail: osmoregulatory and metabolic responses to salinity

Abstract: The Sacramento splittail (Pogonichthys macrolepidotus) is composed of two genetically distinct populations endemic to the San Francisco Estuary (SFE). The allopatric upstream spawning habitat of the Central Valley (CV) population connects with the sympatric rearing grounds via relatively low salinity waters, whereas the San Pablo (SP) population must pass through the relatively high-salinity Upper SFE to reach its allopatric downstream spawning habitat. We hypothesize that if migration through SFE salinities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Changes in salinity can be physiologically stressful to freshwater organisms that even modest increases in salinity can generate consequences that cascade throughout entire ecosystems ( Jones et al ., 2017 ; Verhille et al ., 2020 ; Arnott et al ., 2023 ). Anuran amphibians (frogs and toads) are osmotically sensitive due to highly permeable ectodermal membranes, although there is more variation in salinity tolerance across amphibia than is commonly appreciated ( Hopkins and Brodie, 2015 ; Albecker and McCoy, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in salinity can be physiologically stressful to freshwater organisms that even modest increases in salinity can generate consequences that cascade throughout entire ecosystems ( Jones et al ., 2017 ; Verhille et al ., 2020 ; Arnott et al ., 2023 ). Anuran amphibians (frogs and toads) are osmotically sensitive due to highly permeable ectodermal membranes, although there is more variation in salinity tolerance across amphibia than is commonly appreciated ( Hopkins and Brodie, 2015 ; Albecker and McCoy, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, teleosts use similar strategies to maintain osmotic homeostasis; however, there are also some differences in the regulation of internal water and solute homeostasis [41]. Furthermore, recent studies revealed inter-population differences in fish responses to salinity [42,43]. To address this problem in the present study, cod individuals derived from the western and eastern subpopulations were kept in tanks, where salinity was gradually changed, and then gene expression was measured using a genome-wide DNA oligonucleotide microarray to characterize the putative salinity-regulated genes and the biological and molecular processes involved in salinity adaptation.…”
Section: Introductionmentioning
confidence: 99%